2017
DOI: 10.29314/mlser.v1i1.22
|View full text |Cite
|
Sign up to set email alerts
|

“Dance Dance” Education. A Real “Revolution” for the Classroom?

Abstract: /0000-0002-8355-7239 Universidad de Jaén Resumen. Introducción: La sociedad actual se encuentra en constante evolución en búsqueda de nuevas metodologías educativas que permitan una mejor formación integral del alumnado. Estas deben ser atractivas y motivadoras a la vez que permitan la mejora de las variables cognitivas del alumnado. Por ello, el objetivo de esta presente revisión fue analizar el efecto del Videojuego Activo o Exergame (EX) Dance Dance Revolution (DDR) sobre el rendimiento cognitivo y académic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Dance stimulates non-cognitive abilities; therefore, artistic and social skills are better developed in people who practice this sport compared to those who do not perform any physical activity in their free time [ 27 , 28 ]. Recent studies have demonstrated the effectiveness of including dance in the school curriculum due to its complex effects on children’s growth and development as well as its psychological benefits [ 29 ]. Dance can be practiced with a therapeutic purpose: it improves the health status of people with various mental or motor conditions, increases school or professional results, and prevents the deterioration of brain activity [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dance stimulates non-cognitive abilities; therefore, artistic and social skills are better developed in people who practice this sport compared to those who do not perform any physical activity in their free time [ 27 , 28 ]. Recent studies have demonstrated the effectiveness of including dance in the school curriculum due to its complex effects on children’s growth and development as well as its psychological benefits [ 29 ]. Dance can be practiced with a therapeutic purpose: it improves the health status of people with various mental or motor conditions, increases school or professional results, and prevents the deterioration of brain activity [ 30 ].…”
Section: Introductionmentioning
confidence: 99%